Nature of the Interplay Between Periodontal Diseases and COVID-19 - Cai, Wenji; Marouf, Nadya; Said, Khalid N.; Tamimi, Faleh (Frontiers in Dental Medicine, 2021)
The 2019 coronavirus disease (COVID-19) is mostly a mild condition, however in some patients it could progress into a severe and even fatal disease. Recent studies have shown that COVID-19 infection and severity could be associated with the presence of periodontitis, one of the most prevalent chronic diseases. This association could be explained by the fact that periodontitis and COVID-19 share some common risk factors including chronic diseases such as diabetes and hypertension as well as conditions such as age, sex, and genetic variants. Another possible explanation could be the systemic inflammation and the aspiration of periodontopathogens seen in patients with periodontitis, which could have a synergism with the virus or compromise the reaction of the body against COVID-19. This narrative review explores the nature of these associations, the evidence behind them and their implications.